Perspectives of distance university students against the impact of the Covid-19 phenomenon: Information for decision making - Piñón - Vargas, Mauricio; Flores - Barrera, Aura Paulina; Manríquez - Calderón, Manuel Iván (Universidad Francisco de Paula Santander, 2022)
The objective of this project was to learn about the perspectives of university students on distance education at the Universidad del Valle de Puebla and the Universidad Autónoma del Estado de Hidalgo, delving into the phenomenon during the confinement derived from the pandemic of COVID-19 in Mexico, knowing its characteristics, peculiarities and opportunities for improvement. To establish the objective, the mixed research paradigm with a descriptive cut was used, using the case study methodology in a total population of 660 participants from both institutions. The study was carried out between the months of December 2020 and January 2021, through the use of a questionnaire sent through Google Forms in which the perspectives and experiences of the students in the August - December 2020 semester were investigated in the teaching-learning process. The results obtained describe that the characteristics of the population, the equipment used and acquired in the distance education model, as well as the type of classes that were held allowed us to know that the situations presented were very similar and reflect aspects important to the decisión making.